Thoracolumbar Junction Syndrome Accompanying Renal Artery Stenosis: A Case Repor - Kyudong Noh; Jong Burm Jung; Jeong Won Seong; Doh-Eui Kim; Dongrak Kwon; Yuntae Kim (Annals of Rehabilitation Medicine, 2020)
Flank pain is a common reason for visits to the emergency room. The most common reason warranting hospital visits are urology-related problems. However, there are many other causes, such as musculoskeletal lesions, that difficult to achieve a correct diagnosis. Here, we describe a rare case of flank pain caused by thoracolumbar junction syndrome, accompanying renal artery stenosis. A 54-year-old male with hypertension presented with severe left flank pain for 1 week. Initially, he was diagnosed with left renal artery stenosis by computed tomography and decreased renal function on renal scan (Tc-99m DTPA). Although a stent was inserted into the left renal artery, flank pain persisted with only minor improvement. Through detailed physical examination, he was finally diagnosed with thoracolumbar junction syndrome. After three injections in the left deep paravertebral muscles at the T10–T12 levels, flank pain completely ceased. Clinicians must consider thoracolumbar junction syndrome, when treating patients with flank pain.